SISTEM PENDUKUNG KEPUTUSAN PENEMPATAN PRAKTIK KERJA LAPANGAN MENGGUNAKAN METODE WEIGHT PRODUCT - Intan Fujianti; Heri Haerudin (CV. Multi Kreasi Media, 2024)
In determining the placement of field work practices in the field of computer and network engineering competencies at the Sirajul Falah High School, the head of competency still uses a manual system or method to determine the placement of field work practice (PKL) so that the company is dissatisfied with the results determined by the head of competency. Therefore the authors designed a decision support system based on the method used. Namely utilizing the weight product (wp) method, a method capable of producing more consistent results than other methods, this method is easy to understand and easy to use and provides the easiest solution in the process of determining the placement of field work practice in the field of computer and network engineering competence . This decision support system will greatly assist heads of computer and network engineering in determining placements for field work practices quickly and accurately.